Designing and developing a web tool to support Strategic Environmental Assessment. (January 2019) - González, Dr Ainhoa; Gleeson, Justin; McCarthy, Eoghan
Abstract: Strategic Environmental Assessment (SEA) requires taking into account the sensitivity of the area likely to be affected when identifying and characterising potential impacts resulting from plans and programmes. This entails consideration of the intrinsic characteristics that make the area susceptible to change, and incorporation of stakeholder values and concerns. A geospatial approach to these considerations facilitates identification of potential land-use conflicts and better informs planning decisions. Building on online geoprocessing advancements, we have developed an Environmental Sensitivity Mapping web tool containing novel functionality to support SEA. This paper presents the methodological framework for its participative multi-criteria approach and its architecture, and describes its functionality simulating a practical application. The web tool has the potential to break down data access and specialised skills barriers while providing a means for enhancing SEA consistency and transparency. However, data limitations remain affecting its applicability, and further technological advancements may help enhance its functionality. Highlights: Sensitivity mapping can enhance baseline information for environmental assessments. A novel online geoprocessing tool supports systematic sensitivity assessment. It enables combining context-specific environmental criteria and value judgments. Pilot testing it through stakeholder engagement has validated its applicability. The tool promotes assessment consistency and transparency but data issues remain.